5(2-4)=6h

Simple and best practice solution for 5(2-4)=6h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2-4)=6h equation:



5(2-4)=6h
We move all terms to the left:
5(2-4)-(6h)=0
We add all the numbers together, and all the variables
-6h+5(-2)=0
We add all the numbers together, and all the variables
-6h-10=0
We move all terms containing h to the left, all other terms to the right
-6h=10
h=10/-6
h=-1+2/3

See similar equations:

| m/9+35=-40 | | 3(g-63)=93 | | 7(u+29)=42 | | c/6+47=39 | | 16x²=9 | | n/2+4=-1 | | =14-1/3x | | 9f=2.7 | | 4(x+6)=2-6(x-3) | | 9x=6(x+2)-6=12 | | 13y-9y-13=64.92 | | 7=q/2+6 | | -27x-5=26x | | 16x=15x-11 | | x/9=7/45 | | 3x-x+2=4(2-1) | | 10y-5y-8=60.80 | | 7f=6.3 | | 27=3c-3(6-2c( | | 5/7t+5=2/7t+23 | | 108=4(5a+2) | | 5x-1+3=-12-2x | | 3k-4/2-5k-4/3+1=k-2/3 | | 3k-4/2-5k-4/3+1=k-3/3 | | 3x-x+4=4(2x | | 2x²=12 | | 4a=161/4 | | -3(p+3)-p-2=-4(p+4)+5 | | 34-5x+2(x-2)=25 | | 30k+60k=20k+90 | | 11=-0.5x-5 | | 8q=–9+9q |

Equations solver categories